CISSP Certified Information Systems Security Professional : the Official (ISC)2 CISSP CBK Reference - Deane, Arthur J.; Kraus, Aaron (Sybex, 2021)
The only official, comprehensive reference guide to the CISSP Thoroughly updated for 2021 and beyond, this is the authoritative common body of knowledge (CBK) from (ISC)2 for information security professionals charged with designing, engineering, implementing, and managing the overall information security program to protect organizations from increasingly sophisticated attacks. Vendor neutral and backed by (ISC)2, the CISSP credential meets the stringent requirements of ISO/IEC Standard 17024. This CBK covers the current eight domains of CISSP with the necessary depth to apply them to the daily practice of information security. Revised and updated by a team of subject matter experts, this comprehensive reference covers all of the more than 300 CISSP objectives and sub-objectives in a structured format with: Common and good practices for each objective Common vocabulary and definitions References to widely accepted computing standards Highlights of successful approaches through case studies Whether you've earned your CISSP credential or are looking for a valuable resource to help advance your security career, this comprehensive guide offers everything you need to apply the knowledge of the most recognized body of influence in information security.